2015
DOI: 10.1002/nbm.3299
|View full text |Cite
|
Sign up to set email alerts
|

A study of T 1 relaxation time as a measure of liver fibrosis and the influence of confounding histological factors

Abstract: Liver biopsy is the standard test for the assessment of fibrosis in liver tissue of patients with chronic liver disease. Recent studies have used a non-invasive measure of T1 relaxation time to estimate the degree of fibrosis in a single slice of the liver. Here, we extend this work to measure T1 of the whole liver and investigate the effects of additional histological factors such as steatosis, inflammation and iron accumulation on the relationship between liver T1 and fibrosis. We prospectively enrolled pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
160
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 114 publications
(176 citation statements)
references
References 33 publications
(43 reference statements)
10
160
2
2
Order By: Relevance
“…T1 values have been shown to correlate well with fibrosis and oedema in cardiac [8] and liver imaging [9]. In an animal model of acute kidney injury (AKI) induced by 30min or 45min of ischaemia followed by reperfusion, Hueper et al demonstrated that the T1 relaxation time of renal tissue increased significantly at days 1 and 7, and was associated with renal inflammation [10].…”
Section: T1-mappingmentioning
confidence: 99%
“…T1 values have been shown to correlate well with fibrosis and oedema in cardiac [8] and liver imaging [9]. In an animal model of acute kidney injury (AKI) induced by 30min or 45min of ischaemia followed by reperfusion, Hueper et al demonstrated that the T1 relaxation time of renal tissue increased significantly at days 1 and 7, and was associated with renal inflammation [10].…”
Section: T1-mappingmentioning
confidence: 99%
“…For T 1 measures, the acquisition and analysis are highly repeatable in healthy subjects, with a coefficient of variation between visits of 1.8% and low inter-and intra-observer variability with intra-class correlation coefficients of >0.99 [13] .…”
Section: T 1 Measurements Of Fibrosismentioning
confidence: 99%
“…Two prospective studies have shown that differing measures of liver longitudinal relaxation time (T 1 ) correlate well to histological fibrosis [12,13] . For T 1 measures, the acquisition and analysis are highly repeatable in healthy subjects, with a coefficient of variation between visits of 1.8% and low inter-and intra-observer variability with intra-class correlation coefficients of >0.99 [13] .…”
Section: T 1 Measurements Of Fibrosismentioning
confidence: 99%
See 2 more Smart Citations